High Performance Computing of Complex Electromagnetic Algorithms Based on GPU/CPU Heterogeneous Platform and Its Applications to EM Scattering and Multilayered Medium Structure - Zhe Song; Xing Mu; Hou-Xing Zhou (International Journal of Antennas and Propagation)
The fast and accurate numerical analysis for large-scale objects and complex structures is essential to electromagnetic simulation and design. Comparing to the exploration in EM algorithms from mathematical point of view, the computer programming realization is coordinately significant while keeping up with the development of hardware architectures. Unlike the previous parallel algorithms or those implemented by means of parallel programming on multicore CPU with OpenMP or on a cluster of computers with MPI, the new type of large-scale parallel processor based on graphics processing unit (GPU) has shown impressive ability in various scenarios of supercomputing, while its application in computational electromagnetics is especially expected. This paper introduces our recent work on high performance computing based on GPU/CPU heterogeneous platform and its application to EM scattering problems and planar multilayered medium structure, including a novel realization of OpenMP-CUDA-MLFMM, a developed ACA method and a deeply optimized CG-FFT method. With fruitful numerical examples and their obvious enhancement in efficiencies, it is convincing to keep on deeply investigating and understanding the computer hardware and their operating mechanism in the future.